Development of the sealing method of the pump clearance by well production - Гурбанов, Рамиз Сейфулла; Мамедова, Малейка Агамоглан; Гурбанова, Тюркан Гейдар (Eastern-European Journal of Enterprise Technologies, 2015)
The paper deals with the issues of creating sealing systems in process equipment. The problem of leakage through the clearance of the plunger-cylinder pair of the deep-well pump is considered, and well production is used as a sealing medium. To implement the specified sealing system, the "fluid-fracture" effect, developed by R. S. Gurbanov and M.A. Mamedova is used. The "fluid-fracture" effect at certain critical values of fracture opening leads to changes in the rheological properties of the well production, which allows to identify the pumps with the necessary clearances for the production to work as a seal. The developed method allows to reduce the delivery rate of the pump and decrease the cost of pumps used in a single well.